PENINGKATAN KEMAMPUANBERPIKIRKRITISMELALUI METODE PROBLEM SOLVING PADA PESERTA DIDIK X KU 3 SMKN 1 LUMAJANG - Susiyati - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
This study aims to: (1) improve the students’ critical thinking skills through the implementation of problem solving learning methods using media information, and (2) prove the improvement of the students’ critical thinking skills after the implementation of problem solving learning methods using media information. The research design used in this study was a classroom action research that has been completed in two cycles. The type of action taken is learning Productive Marketing with media-assisted method of problem solving information. The findings show that there is an improvement on the students’ critical thinking skills. The lowest improvement is in the aspect Defining Problems; whereas, the highest improvement is in the aspect of Look and Learn. In the first cycle, the learning outcomes of students showed a maximum value of 95, the average score = 75.4 and a minimum score = 55. In the second cycle the resulted score showed a maximum score was 100, the average value of 80.4 and a minimum value of 70. In the first cycle there are 30 learners who get 73% of the criterion of minimum completeness; whereas, in the second cycle 100%. Thus the problem solving method using information media can be very effective to improve the students’ critical thinking skills at class X Productive Marketing KU 3, SMK 1 Lumajang.Keywords: methods of problem solving, critical thinking skills.